Unconventional methods of analysing diode rectifiers with asymmetrical supply - Olszowiec, Piotr (Publishing House of Lviv Polytechnic National University, 2014)
Output voltage parameters of diode rectifiers such as mean and root mean square (RMS) value are decisive for proper operation of DC systems fed from these rectifiers. It is necessary to know these parameters for the assessment of the operation conditions of these systems. In the paper a formula for the output voltage of three-phase diode rectifiers fed by asymmetrical voltages is derived. The derivation of a universal formula for an output voltage mean value of nphase diode rectifiers with the use of the mathematical induction method is also presented. Такі параметри вихідної напруги діодних випрямлячів, як середнє та середньоквадратичне значення є вирішальними для правильного функціонування систем постійного струму, які живляться від цих випрямлячів. Необхідно знати ці параметри для оцінювання умов роботи таких систем. У статті виведено формулу вихідної напруги для трифазного діодного випрямляча, який живиться асиметричною напругою. Також тут представлено виведення універсальної формули для середнього значення вихідної напруги для n-фазного діодного випрямляча з використанням методу математичної індукції.
Нестандартніметоди аналізу діодних випрямлячів з асиметричним джерелом живлення
Keywords: three-phase diode rectifiers; asymmetrical supply voltages; mean value; output voltage; mathematical induction method